The Auxiliary Equation Because Dx(erx) = rerx, it seems likely that erx will
be a solution to our differential equation for an appropriate choice of r. To test this
possibility, we first write the equation in the operator form
(1) (D2 + a1D + a2 )y = 0
Now
(D2 + a1D + a2)erx = D2(erx) + a1D(erx) + a2 erx
= r2erx + a1rerx + a2erx
= erx (r 2 + a1r + a2)
The latter expression is zero, provided
(2) r2 + a1r + a2 = 0
Equation (2) is called the auxiliary equation for (1) (note the similarity in
form). It is an ordinary quadratic equation and can be solved by factoring or, if
necessary, by the Quadratic Formula. There are three cases to consider, correspon-
ding to whether the auxiliary equation has two distinct real roots, a single repeated
root, or two complex conjugate roots.
y = C1er1x + C2er2x
This is all fine if the auxiliary equation has distinct real roots. But what if it has
the form
r2 - 2r1 r + r21 = (r - r1)2 = 0
Then our method produces the single fundamental solution er1x and we must find
another solution independent of this one. Such a solution is xer1x, as we now
demonstrate.
(D2 - 2r1 D + r21)xer1x = D2(xer1x) - 2r1 D(xer1x) + r21 xer1x
= (xr21 er1x + 2r1 er1x) - 2r1(xr1 er1x + er1x) + r21 xer1x
= 0
y = C1er1x + C2xer1x
Summary
Consider the second-order differen- ■ EXAMPLE 3 Solve y– - 6y¿ + 9y = 0.
tial equation SOLUTION The auxiliary equation has 3 as a repeated root. Thus,
y– + a1y¿ + a2 = 0 y = C1e3x + C2xe3x ■
with auxiliary equation
Finally, we consider the case where the auxiliary equation has complex conju-
r2 + a1r + a2 = 0 gate roots. The simple equation
The latter equation may have two (D2 + b 2)y = 0
real roots r1 and r2, one real root r1,
or two complex roots a ; bi.
with auxiliary equation r2 + b 2 = 0 and roots ; bi offers a hint. Its fundamental
solutions are easily seen to be sin bx and cos bx. You can check by direct differen-
Solution to tiation that the general situation is as follows.
Roots Differential Equation
Theorem C Complex Conjugate Roots
r1 Z r2 y = C1 er1x + C2 er2x
r1 = r2 y = C1 er1x + C2 xer1x
If the auxiliary equation has complex conjugate roots a ; bi, then the general
a ; bi y = C1 e ax
cos bx
solution of y– + a1 y¿ + a2 y = 0 is
+ C2 eax sin bx y = C1eax cos bx + C2eax sin bx
778 Chapter 15 Differential Equations
Concepts Review
1. The auxiliary equation corresponding to the differential 3. The general solution to (D2 - 2D + 1) y = 0 is y =
equation (D2 + a1 D + a2) y = 0 is ________ . This equation ________ .
may have two real roots, a single repeated root, or ________ .
4. The general solution to (D2 + 1) y = 0 is y = ________ .
2. The general solution to (D2 - 1)y = 0 is y = ________ .
21. Solve x2 y– + 5xy¿ + 4y = 0 by first making the substi- 26. Let the roots of the auxiliary equation r2 + a1r + a2 = 0
tution x = ez. be a ; bi. From Problem 25c, it follows, just as in the real case,
22. Show that the substitution x = ez transforms the Euler that y = c1e(a ; bi)x + c2e(a–bi)x satisfies (D2 + a1D + a2)y = 0.
equation ax2 y– + bxy¿ + cy = 0 to a homogeneous linear Show that this solution can be rewritten in the form
equation with constant coefficients. y = C1eax cos bx + C2eax sin bx
23. Show that if r1 and r2 are distinct real roots of the auxil-
iary equation, then y = C1er1x + C2er2x is a solution of giving another approach to Theorem C.
y– + a1 y¿ + a2 y = 0.
CAS Use a CAS to solve each of the following equations:
24. Show that if a ; bi are complex conjugate roots of the
auxiliary equation, then y = C1eax cos bx + C2eax sin bx is a so- 27. y– - 4y¿ - 6y = 0; y(0) = 1, y¿(0) = 2
lution of y– + a1y¿ + a2 y = 0. 28. y– + 5y¿ + 6.25y = 0; y(0) = 2, y¿(0) = -1.5
25. Recall that complex numbers have the form a + bi, 29. 2y– + y¿ + 2y = 0; y(0) = 0, y¿(0) = 1.25
where a and b are real. These numbers behave much like the
30. 3y– - 2y¿ + y = 0; y(0) = 2.5, y¿(0) = -1.5
real numbers, with the proviso that i2 = -1. Show each of the
following:
(a) ebi = cos b + i sin b Hint: Use the Maclaurin series for eu,
cos u, and sin u. Answers to Concepts Review: 1. r2 + a1 r + a2 = 0; com-
(b) ea + bi = ea(cos b + i sin b) plex conjugate roots 2. C1e -x + C2ex 3. (C1 + C2x)ex
4. C1 cos x + C2 sin x
(c) Dx e(a + bi)x = (a + bi)e(a + bi)x
15.2 Consider the general nonhomogeneous linear equation with constant coefficients
Nonhomogeneous (1) y(n) + a1y(n–1) + Á + an–1y¿ + any = k(x)
Equations Solving this equation can be reduced to three steps:
1. Find the general solution
yh = C1u1(x) + C2u2(x) + Á + Cnun(x)
to the corresponding homogeneous equation (i.e., equation (1) with k(x)
being identically zero), as described in Section 15.1.
2. Find a particular solution yp to the nonhomogeneous equation.
3. Add the solutions from Steps 1 and 2.
We state the result as a formal theorem.
Theorem A
If yp is any particular solution to the nonhomogeneous equation
Proof The linearity of the operator L is the key element in the proof. Let yp and
yh be as described. Then
L(yp + yh) = L(yp) + L(yh) = k(x) + 0
and so y = yp + yh is a solution to (2).
Conversely, let y be any solution to (2). Then
If k(x) = Try yp =
To illustrate the table, we suggest the appropriate trial solution yp in six cases.
The first three are straightforward; the last three are modified because a term on
the right side of the differential equation is present in the solution to the homoge-
neous equation.
yp = Ax2 + Bx + C
SOLUTION Combining the results of Examples 2 and 3 and using the linearity
of the operator D2 - 2D - 3, we obtain
7 4
y = 2xe3x - cos 2x - sin 2x + C1e -x + C2e3x ■
65 65
v2(x) = dx = x
L
(We can omit the arbitrary constants in the above integrations, since any solutions
v1 and v2 will do.) A particular solution is therefore
yp = (ln ƒ cos x ƒ ) cos x + x sin x
a result that is easy to check by direct substitution in the original differential equa-
tion. We conclude that
y = (ln ƒ cos x ƒ ) cos x + x sin x + C1 cos x + C2 sin x ■
Concepts Review
1. The general solution to a nonhomogeneous equation has 3. The method of undetermined coefficients suggests trying
the form y = yp + yh, where yp is a ________ and yh is the gener- a particular solution of the form y = __________________ for
al solution to the ________. y– - y¿ - 6y = x2.
2. Thus, after noting that y– - y¿ - 6y = 6 has the particu- 4. The method of undetermined coefficients suggests trying
lar solution y = -1, we conclude that the general solution is a particular solution of the form y = __________________ for
y = ________. y– - y¿ - 6y = e3x.
Section 15.3 Applications of Second-Order Equations 783
d2y
+ B2y = 0
y dt2
Simple harmonic motion
and has the general solution
y0
y = C1 cos Bt + C2 sin Bt
t
The conditions y = y0 and y¿ = v0 at t = 0 determine the constants C1 and C2. If
the object is released with an initial velocity of 0, then C1 = y0 and C2 = 0. Thus,
2π
Period = B y = y0 cos Bt
We say that the spring is executing simple harmonic motion with amplitude y0 and
Figure 2 period 2p>B (Figure 2).
784 Chapter 15 Differential Equations
SOLUTION The first sentence of the example allows us to determine the spring
constant. By Hooke’s Law, ƒ F ƒ = ks, where s is the amount in feet that the spring is
stretched, and so 5 = k(12), or k = 10. Now put the origin at the equilibrium point
after the 20-pound weight has been attached. From the derivation just before the
example, we know that y = y0 cos Bt. In the present case, y0 = 2 and
B2 = kg>w = (10)(32)>20 = 16. We conclude that
y = 2 cos 4t
w d2y dy
= -ky - q . k 7 0, q 7 0
g dt2 dt
d 2y dy
2
+ E + B2y = 0
dt dt
an equation for which the methods of Section 15.1 apply. The auxiliary equation
for this second-order linear differential equation is r2 + Er + B2 = 0, so the roots
are
-E ; 2E 2 - 4B2
2
We must consider the cases where E 2 - 4B2 is negative, zero, and positive.
The factor e -at, called the damping factor, causes the amplitude of the motion
to approach zero as t : q (Figure 3a). ■
Section 15.3 Applications of Second-Order Equations 785
y y y
x x x
Figure 3
Case 2: E2 - 4B2 = 0 In this case, the auxiliary equation has the double root
-a where a = E>2 and the general solution of the differential equation is
y = C1e -at + C2te -at
The motion described by this equation is said to be critically damped. ■
Case 3: E2 - 4B2 7 0 The auxiliary equation has roots -a1 and -a2, and the
general solution of the differential equation is
y = C1e -a1t + C2e -a2t
It describes a motion that is said to be overdamped.
The graphs in the critically damped and overdamped cases cross the t-axis at
most once and may look something like Figure 3b or 3c. ■
Figure 4 The current I = dQ>dt, measured in amperes, satisfies the equation obtained by
differentiating equation (1) with respect to t; that is,
d2I dI 1
(2) L 2
+ R + I = E¿(t)
dt dt C
These equations can be solved by the methods of Sections 15.1 and 15.2 for many
functions E(t).
786 Chapter 15 Differential Equations
d2Q dQ
2
+ 800 + 250,000Q = 600
dt dt
The auxiliary equation has roots
Concepts Review
1. A spring that vibrates without friction might obey a law 3. If the friction is very great, the law of motion might take
of motion such as y = 3 cos 2t. We say it is executing simple har- the form y = 3e -0.1t + te -0.1t, the critically damped case, in which
monic motion with amplitude ________ and period ________. y slowly fades to ________ as time increases.
2. A spring vibrating in the presence of friction might obey 4. Kirchhoff’s Law says that a(n) ________ satisfies a
a law of motion such as y = 3e -0.1t cos 2t, called damped har- second-order linear differential equation.
monic motion. The “period” is still ________ , but now the ampli-
tude ________ as time increases.
9. Using Figure 5, find the charge Q on the capacitor as a (a) Show that the equation of motion for A Z B is
function of time if S is closed at t = 0. Assume that the capacitor c
is initially uncharged. y = C1 cos Bt + C2 sin Bt + sin At
B - A2
2
Figure 5 16. Show that the motion of part (a) of Problem 14 is period-
ic if B>A is rational.
10. Find the current I as a function of time in Problem 9 if the 17. Refer to Figure 9, which shows a pendulum bob of mass m
capacitor has an initial charge of 4 coulombs. supported by a weightless wire of length L. Derive the equation
11. Use Figure 6. of motion; that is, derive the differential equation satisfied by u.
Suggestion: Use the fact from Section 11.7 that the scalar tangen-
(a) Find Q as a function of time. Assume that the capacitor is
tial component of the acceleration is d2s>dt2, where s measures
initially uncharged.
arc length in the counterclockwise direction.
(b) Find I as a function of time.
C # 2 "10–6 F θ
E # 120
sin 377t L
Figure 6
S
L = 10–2 H 18. The equation derived in Problem 17 is nonlinear, but for
small u it is customary to approximate it by the equation
E = 20 V C = 10–7 F d 2u g
2
+ u = 0
dt L
Figure 7 2
Here g = GM>R , where G is a universal constant, M is the mass
of the earth, and R is the distance from the pendulum to the cen-
13. Using Figure 8, find the steady-state current as a function
ter of the earth. Two clocks, with pendulums of length L1 and L2
of time; that is, find a formula for I that is valid when t is very
and located at distances R1 and R2 from the center of the earth,
large (t : q ).
have periods p1 and p2, respectively.
R = 1000 Ω p1 R1 2L1
(a) Show that = .
p2 R2 2L2
(b) Find the height of a mountain if a clock that kept perfect
L = 3.5 H
time at sea level (R = 3960 miles) with L = 81 inches had
to have its pendulum shortened to L = 80.85 inches to keep
E # 120
C # 2 " 10–6 F perfect time at the top of the mountain.
sin 377t